2004
DOI: 10.1128/cdli.11.1.211-215.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Babesia caballi Gene Encoding the 134-Kilodalton Protein and Evaluation of Its Diagnostic Potential in an Enzyme-Linked Immunosorbent Assay

Abstract: A Babesia caballi gene encoding the 134-kDa (BC134) protein was immunoscreened with B. caballi-infected horse serum. An enzyme-linked immunosorbent assay (ELISA) using recombinant BC134 protein could effectively differentiate B. caballi-infected horse sera from Babesia equi-infected or noninfected control horse sera. These results suggest that the recombinant BC134 protein is a potential diagnostic antigen in the detection of B. caballi infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The MAEBL is an erythrocyte-binding protein located in the rhoptries and on the surface of mature merozoites; it is expressed at the beginning of schizogony (3,18). P200 was previously identified as a diagnostic antigen for the serological detection of B. bigemina infection and also has a glutamic acid-rich region, as does the Be158 protein (23). Taken together, these findings indicate that the Be158 gene product might be a novel candidate for a vaccine molecule as well as a diagnostic antigen for B. equi infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MAEBL is an erythrocyte-binding protein located in the rhoptries and on the surface of mature merozoites; it is expressed at the beginning of schizogony (3,18). P200 was previously identified as a diagnostic antigen for the serological detection of B. bigemina infection and also has a glutamic acid-rich region, as does the Be158 protein (23). Taken together, these findings indicate that the Be158 gene product might be a novel candidate for a vaccine molecule as well as a diagnostic antigen for B. equi infection.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting plasmid, designated pGEX/Be158, was used to transform the E. coli BL21 strain (Stratagene, La Jolla, Calif.) and express the recombinant Be158 gene product fused with glutathione S-transferase (GST), designated GST/Be158 protein, by standard techniques (21). The GST/Be158 protein was purified from the soluble fraction with glutathione-Sepharose 4B (Amersham Pharmacia Biotech), as described previously (9,14,23).…”
Section: Methodsmentioning
confidence: 99%
“…Currently, recombinant proteins are used to detect the infection rather than using a serological test with a crude antigen prepared from merozoites [7,18]. A previous study by Ikadai et al, [22] concluded that the 48-kDa protein is immunodominant and might be an important antigen for diagnosis and was reported to be involved in the invasion of erythrocytes [13] and to differentiate very clearly between B. caballi-infected horse sera, and T. equi-infected horse sera. Moreover, an ELISA using a newly identified rBC134 protein was developed and proved to be highly specific for the detection of B. caballi-specific equine antibodies [23].…”
Section: Plos Onementioning
confidence: 99%
“…Bc48 is one rhoptry protein of merozoites of B. caballi, which was previously evaluated as a promising antigen for the serological detection of antibodies of B. caballi [12]. Moreover, BC134 protein was developed and proved to be highly specific for the detection of B. caballispecific equine antibodies [13].…”
Section: Introductionmentioning
confidence: 99%
“…Various genetic markers have been employed for the differentiation and characterization of B. caballi, comprising the BC48 and 134 protein genes (Tomaki et al, 2004), the rhoptryassociated protein (RAP-1) gene , the 16 S rRNA gene and 18S rRNA gene . Of all these genes, the 18S rRNA gene remained the most common target gene in various investigations.…”
Section: In Babesia Caballi Speciesmentioning
confidence: 99%